An Analysis of English Teacher Readiness in Implementing Merdeka Curriculum at MTs Negeri 3 Banyumas - Mutmainah Fahmi Karimatunisa; Endang Sartika (Yayasan Pendidikan Penelitian Pengabdian Algero, 2024)
The Merdeka Curriculum has begun to be implemented in a two-year trial period since 2022/2023 academic year and required teacher readiness in running it. This research aims to analyze the English teacher readiness in implementing Merdeka Curriculum at MTs Negeri 3 Banyumas. This research used descriptive qualitative method. The object of this research was the readiness of English teacher and the subjects were 7th and 8th grade English teachers who teach using the Merdeka Curriculum Implementation. The data were collected through interview, documentation, and observation. Data analysis was carried out with Miles and Huberman’s theory, which consists of three steps, namely data condensation, data display, and data conclusion. The result of this research showed that English teachers fulfilled 6 out of 9 indicators used to determine the teacher readiness. All three teachers already understand the characteristic and structure of the curriculum, plan the diagnostic assessment, adjust the learning with the stage of achievements and characteristic of students, plan, implement and process formative and summative assessment, focus on essential material, and conduct the flexible learning. Two indicators were not fulfilled by the three teachers, those were compiling the teaching module and implementing the project-based learning. While, only one teacher developed the teaching module.